2009
DOI: 10.1007/bf03218916
|View full text |Cite
|
Sign up to set email alerts
|

Effect of γ-Ray irradiation on surface oxidation of ultra high molecular weight polyethylene/zirconia composite prepared byin situ ziegler-natta polymerization

Abstract: Novel ultra-high molecular weight polyethylene (UHMWPE)/zirconia composites were previously prepared by the in situ polymerization of ethylene using a Ti-based Ziegler-Natta catalyst supported on to the surface of zirconia, as a bearing material for artificial joints. Tribological tests revealed that a uniform dispersion of zirconia in UHMWPE markedly increased the wear resistance. The effects of zirconia content on the oxidation behavior of the γ-ray-treated UHMWPE/zirconia composite surfaces were examined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…After curve‐fitting, the peak of the C 1s electrons at 284.50 eV, shown in Figure (b,c), corresponded with the CC and CH bonds of the UHMWPE in both the DW and NS lubricating conditions . The small peaks from 286.00 to 289.00 eV (those at 286.65, 287.70, and 289.00 eV corresponded to the CO, CO, and OCO groups, respectively) indicated the formation of surface photooxidation products caused by air . Moreover, the spectra showed that the film contained oxygen in addition to carbon.…”
Section: Resultsmentioning
confidence: 96%
“…After curve‐fitting, the peak of the C 1s electrons at 284.50 eV, shown in Figure (b,c), corresponded with the CC and CH bonds of the UHMWPE in both the DW and NS lubricating conditions . The small peaks from 286.00 to 289.00 eV (those at 286.65, 287.70, and 289.00 eV corresponded to the CO, CO, and OCO groups, respectively) indicated the formation of surface photooxidation products caused by air . Moreover, the spectra showed that the film contained oxygen in addition to carbon.…”
Section: Resultsmentioning
confidence: 96%
“…Fabricating UHMWPE-based composite, using different types of additives such as HA [9], Carbon Nanofibers [10], Carbon Nanotubes [11], Zirconia [12,13], and Alumina [14] or even using some additives such as Zirconia and HA at the same time [15] in order to reduce the wear rate of this polymer has been widely investigated. Recent evidence suggests that the powder mixing method and the fabrication method may significantly impact the final composites' properties [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] One of the major issues on polymer scratch study is the standardization of test methodologies and appropriate evaluation techniques that can precisely quantify the scratch damage on polymer surfaces. [1][2][3][4] In recent years, two global test methods for obtaining meaningful and reproducible results on the scratch behaviors of polymers have been proposed. One is an ASTM standard (D7027-05).…”
Section: Introductionmentioning
confidence: 99%